The Americanization of Europe : culture, diplomacy, and anti-Americanism after 1945 - Stephan, Alexander, 1946-2009 (Berghahn Books, 2006)
"Recent tensions between the U.S. and Europe seem to have opened up an insuperable rift, while Americanization, deplored by some, welcomed by others, seems to progress unabated. This volume explores, for the first time and in a comparative manner, the role American culture and anti-Americanism play in eleven representative European countries, including major powers like Great Britain, France, (West) Germany, Russia/Soviet Union, and Italy as well as smaller countries like Austria, Denmark, Greece, Spain, Sweden, and Poland. Each contributor to the volume, all of them highly respected experts in their field, was asked to address the following four topics: the role of American public diplomacy, the transfer of American 'high culture, ' the impact of 'popular culture' ranging from Hollywood movies and TV to pop music and life-style issues, and the country specific features and history of anti-Americanism. The volume is enhanced by a substantial introduction by the editor, which looks both at the general 'culture clash' between the United States and Europe and at adaptations and blending processes that seem to have occurred in individual countries."--